Home bitter home: How labor protection influences firm offshoring - Weng, D.; Peng, Mike (Pergamon, 2018)
Drawing on the home country literature, we argue that firms headquartered or located in countries with strong labor protection may face challenges in their domestic operations. These firms are likely to initiate offshoring to enhance operational efficiency. Building on this argument, we also examine the boundary conditions moderating this proposed effect including labor productivity and employee stock ownership. Results based on a sample of information technology firms operating within five developed countries during 1990–2010 provide support for these arguments. These findings suggest that offshoring can be a partial exit strategy for firms to address the institutional challenges in their home country.